Anime's Media Mix : Franchising Toys and Characters in Japan - Steinberg, Marc, 1977- (Book collections on Project MUSE., 2012)
In Anime's Media Mix, Marc Steinberg convincingly shows that anime is far more than a style of Japanese animation. Engaging with film, animation, and media studies, as well as analyses of consumer culture and theories of capitalism, Steinberg offers the first sustained study of the Japanese mode of convergence that informs global media practices to this day.